2021
DOI: 10.3389/fcvm.2021.788194
|View full text |Cite
|
Sign up to set email alerts
|

Examining Optimism, Psychosocial Risks, and Cardiovascular Health Using Life's Simple 7 Metrics in the Multi-Ethnic Study of Atherosclerosis and the Jackson Heart Study

Abstract: Background: Optimism has been shown to be positively associated with better cardiovascular health (CVH). However, there is a dearth of prospective studies showing the benefits of optimism on CVH, especially in the presence of adversities, i.e., psychosocial risks. This study examines the prospective relationship between optimism and CVH outcomes based on the Life's Simple 7 (LS7) metrics and whether multilevel psychosocial risks modify the aforementioned relationship.Methods: We examined self-reported optimism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 93 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…Our results are in line with findings from a cross-sectional analysis with individuals aged 18–85 years, in which low life satisfaction (≤1 on a scale from 0 to 4) was associated with a lower chance of achieving optimal and intermediate levels of global ideal CVH in women (Mathews et al, 2018). Although few studies have investigated the association of life satisfaction with global ideal CVH, previous longitudinal studies showed consistent associations of positive affect (Boehm et al, 2020), subjective well-being (Boehm et al, 2017), and high levels of optimism (Park et al, 2021; Sims et al, 2019) with higher levels of ideal CVH, even after adjustments for sociodemographic characteristics and depression. This evidence suggests that higher levels of life satisfaction can contribute to improving CVH.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results are in line with findings from a cross-sectional analysis with individuals aged 18–85 years, in which low life satisfaction (≤1 on a scale from 0 to 4) was associated with a lower chance of achieving optimal and intermediate levels of global ideal CVH in women (Mathews et al, 2018). Although few studies have investigated the association of life satisfaction with global ideal CVH, previous longitudinal studies showed consistent associations of positive affect (Boehm et al, 2020), subjective well-being (Boehm et al, 2017), and high levels of optimism (Park et al, 2021; Sims et al, 2019) with higher levels of ideal CVH, even after adjustments for sociodemographic characteristics and depression. This evidence suggests that higher levels of life satisfaction can contribute to improving CVH.…”
Section: Discussionmentioning
confidence: 96%
“…A cross-sectional study found an inverse association between life satisfaction and the Framingham Risk Score in Polish adults (Lopuszan ́ska et al, 2013). Furthermore, the way to analyze the ideal CVH score varies among studies: some use the global score, while others assess the lifestyle and biological subscales separately (Mathews et al, 2018;Park et al, 2021). Studies using subscales indicate that there may be differences in associations, especially in outcomes of a subjective or mental/cognitive health nature (Gaye et al, 2016;Sabia et al, 2019).…”
mentioning
confidence: 99%
“…There has been a positive association between optimism and better health behaviors, including better dietary and physical activity habits. 20 , 21 In addition, associations between optimism and physical function are found in multiple pathophysiologic mediators of chronic disease, including inflammation, impairments in endothelial function, metabolic activity, blood pressure, ambulatory blood pressure, and hypothalamic‐pituitary‐adrenocortical function. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Since the establishment of the LS7, studies have developed scoring algorithms that classify and categorize study subjects based on achieving these established goals [ 2 ]. Better cardiovascular health (CVH), as assessed by the LS7, has shown protective associations with all-cause and cardiovascular mortality [ 3 , 4 , 5 ], incidence of cardiovascular events [ 2 , 6 ], cancer risk [ 2 ], aging-related declines in physical [ 7 , 8 ] and cognitive function [ 9 , 10 , 11 ], frailty [ 12 ], and psychosocial health and depression [ 13 , 14 , 15 ]. Taken together, these findings suggest that CVH captures biological age, and this notion is also supported by CVH being associated with the epigenetic clock [ 16 , 17 ], one of the widely studied molecular biomarkers of biological age.…”
Section: Introductionmentioning
confidence: 99%